Influence of some chemical characteristics on the use of chlorine-containing solutions as root canal irrigants - Rossi-fedele, Giampiero (2013)
Aim : the goal of the present investigation was to look into chemical interactions and characteristics, other than chlorine concentration, and their effect on the overall performance of chlorine-containing root canal irrigants. Methodology : Three different searches were performed in the Medline electronic database, with the purpose of identifying publications that: (a) reviewed the influence of pH changes on the efficacy of chlorine-containing endodontic irrigating solutions; (b) studied unwanted chemical interactions between sodium hypochlorite (NaOCl), chlorhexidine (CHX), EDTA and Citric acid; (c) compared NaOCl alone and NaOCl modified with the addition of a surface-active agent in endodontics. A hand search of articles published online, and appearing in the reference list of the articles included (for search c only), was further performed, using the same search criteria as the electronic search. Four investigations were carried out: (a) to evaluate the antimicrobial effect of Sterilox and sodium hypochlorite against Enterococcus faecalis in a bovine root canal model; (b) to evaluate the bovine pulp tissue dissolution ability of Sterilox, HealOzone, and 0.5% sodium hypochlorite, used alone or in combination; (c) to understand the effect of storage conditions on Sterilox s stability. Eight bottles (four completely full, four half-full) of freshly prepared solution were divided into four groups and subsequently stored by being either exposed to or protected from sunlight; (d) to evaluate whether the immersion of CHX impregnated guttapercha points in chlorine-containing endodontic irrigants causes colour changes and precipitate formation, eighty-one CHX medicated points were immersed in microtubes, containing the following solutions: 0.5 and 5.25% NaOCl or Aquatine (Sterilox). The samples were visually assessed by two independent observers at regular intervals over three weeks to detect colour changes and precipitate formation. Results : The searches identified: for topic a: 1304 publications, 20 fulfilled the inclusion/exclusion criteria; for topic b: 1285 publications, 19 fulfilled the inclusion/exclusion criteria; for topic c: 302 publications 11 fulfilled the inclusion/exclusion criteria. For investigation a: statistically significant differences between the groups exposed to sunlight and non-exposed groups (p <0.001) were found, whilst the presence of air did not affect the chlorine decomposition in the bottles. For investigation b: the groups containing 5.25% NaOCl started to produce a visible precipitate after fourteen days (16.48 ± 0.98) for the impregnated points; no other test group presented with changes. Conclusions : Regarding investigation (a), on antimicrobial efficacy, NaOCl appears to be the best preparation amongst chlorine-containing irrigants; this can be enhanced by reducing its pH. Interactions with chelating agents can reduce this action, and there is no clear evidence regarding the effect of surface-tension modification. Investigation (b) on tissue dissolution ability showed that NaOCl is the only chlorine-containing solution with a clinically relevant action. Sodium hypochlorite dissolution ability may be speeded up with the adjunct use of ozone. The literature reviews also pointed out that interaction with chelators reduce this ability, whilst the surface tension of the preparations has no influence. By mixing NaOCl and CHX in liquid or gel forms, a precipitate is formed; this is likely to contain a cancerogenic substance. Investigation (c) showed that Sterilox chlorine concentration is stable for a twoweek period if protected from direct sunlight; if exposed to sunlight the degradation process started after 4 days. Investigation (d) allowed stating that the placement of impregnated guttapercha points in 5.25% NaOCl for a two-week period caused the formation of a precipitate in the experimental conditions of this study.